Pengembangan Wisata Religi Sebagai Pariwisata Berkelanjutan di Kota Pasuruan - Arsvendo, Dimas; Khotimah, Khusnul; Fitrianto, Achmad Room (JURNAL MASTER PARIWISATA; Volume 09, Nomor 01, Juli 2022DO - 10.24843/JUMPA.2022.v09.i01.p05, 2022)
This research aims to make the development of religious tourism as sustainable tourism in the city of Pasuruan. This research includes qualitative research, using the methods of observation, interviews, literature study and documentation as a method for data collection. Based on the research conducted, it is found that Pasuruan City is a city that has potential in developing sustainable tourism through the development of religious tourism. With the development of sustainable tourism, it can contribute to the regional economy and the people of Pasuruan and can become an icon of Pasuruan. It is hoped that this research can help the Pasuruan city government in carrying out tourism development to improve the regional economy of Pasuruan city. Keywords: tourism, sustainable tourism, religious tourism, pasuruan city.